(untitled) (International Journal of Environmental Sciences, 2025)
Hepatitis B virus (HBV) infection continues to remain a significant global health problem. Estimates of the World Health Organization (WHO) suggest that more than 2 billion people worldwide have been infected with HBV. Of these, approximately 240 million individuals have chronic (long-term) liver infections and at risk of serious illness and death, mainly from liver cirrhosis and hepatocellular carcinoma (HCC). More than 780000 people die every year due to the acute or chronic consequences of hepatitis B. In present research work, Telbivudine loaded solid lipid nanoparticles were prepared by emulsification- Sonification method with slight modification. The Optimization was done by design of expert (Design Expert TM Software). Total 36 batches were prepared by using different types of lipids, type of surfactant and concentration of surfactant and it was optimized on basis of entrapment efficiency and particle size. The optimized formulation was evaluated for Zeta potential and particle morphology by SEM and further it is modified by galactose for active targeting (GmSLN) The GmSLN was further evaluated by In-Vitro Hepatoprotective activity and ex vivo cellular uptake studies. Hepatoprotective activity was performed against DCFH-hepatotoxicity using HepG2 Liver cell lines. The Cellular Uptake Studies was performed using Hepa-1c1c7 cells. The results of Hepatoprotective activity against DCFH-hepatotoxicity showed that DCFH-toxicated cells were recovered to about 67% and 86% upon treatment with 200 µg/ml of SLN and GA modified SLN, respectively. The time dependent cellular uptake is also studied which reveals that GA- modified system shows better uptake in less time as compared to Plain SLN which proves that modification increases uptake in hepatocyte cells after modification with galactose.